Socio-ecological value chain resilience and cleaning workers. (2nd January 2023) - Tödt, Sara; Chan Unger, Carla; Moolchand, Ema; Marshall, Shelley
ABSTRACT: Examining the ways that industries survived the COVID-19 pandemic can teach us a great deal about the resilience of value chains, the ways value chain dynamics shape worker resilience, and the measures states can adopt to support both. In this paper we critically examine the thriving body of theory known broadly as supply chain resilience and explore a branch that embraces socio-ecological perspectives. We first develop a theoretical model that takes what we perceive to be the most fruitful elements of these literatures for industrial relations scholarship and bring it together with approaches tangential to industrial relations concerned with value chain actor and worker agency and resilience. We then apply this model in an analysis of the Australian commercial cleaning sector during the pandemic. Finally, we assess federal and state measures to assist and "buffer" employment and the economy in Australia, including JobKeeper and JobSeeker. We find that these government measures, combined with earlier restructuring of the labour market and restrictive immigration policies, provided the institutional scaffolding for the failure of the cleaning industry during the pandemic, exactly when cleaning became an essential service for the resilience of the whole of society.